2017
DOI: 10.1007/s00501-017-0638-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Laboratory Studies of Conventional and Electrodynamic Fragmentation of an Industrial Mineral

Abstract: Abstract:In order to address comminution efficiency, which could be defined as the increase in mass specific surface against net specific energy input, the energy consumption of an industrial mineral with and without preweakening by high voltage pulses covering the same size range were compared. The three tested comminution sequences consisted of a laboratory jaw crusher or pilot scale high voltage pulse machine at two different circulating loads, a laboratory crusher and two tumbling mills of differing grindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…This improvement of the grindability with the EPF treatment is no longer noticeable however when performing the Bond ball mill work index ( Table 3 ). This corresponds with Tschugg et al (2017) , which showed that EPF treatment can result in energy savings in the comminution step directly after EPF, however did not observe additional energy savings subsequently in the comminution flow sheet, most likely due to the fracture network generated during EPF being consumed immediately in the next comminution step. Another explanation for these results is material specific, in that the Bond ball mill work index is not appropriate for exhibiting the weakening effect of the EPF technology when the major gangue mineral liberation size is coarser than the closing screen size used for the Bond ball mill test (usually around 100 µ m).…”
Section: Table Footnotessupporting
confidence: 72%
See 1 more Smart Citation
“…This improvement of the grindability with the EPF treatment is no longer noticeable however when performing the Bond ball mill work index ( Table 3 ). This corresponds with Tschugg et al (2017) , which showed that EPF treatment can result in energy savings in the comminution step directly after EPF, however did not observe additional energy savings subsequently in the comminution flow sheet, most likely due to the fracture network generated during EPF being consumed immediately in the next comminution step. Another explanation for these results is material specific, in that the Bond ball mill work index is not appropriate for exhibiting the weakening effect of the EPF technology when the major gangue mineral liberation size is coarser than the closing screen size used for the Bond ball mill test (usually around 100 µ m).…”
Section: Table Footnotessupporting
confidence: 72%
“…However, when comparing not the whole particle size range but only particles smaller than 1 mm ( Fig. 9), it can be observed that conventional crushing led to the production of a higher amount of fine particles compared to the EPF technology, as already observed by Tschugg and al. (2017).…”
Section: Characterization Of the Products Obtained After The Two Epf supporting
confidence: 68%